A STUDY ON ACCEPTANCE AND COMPLIANCE OF DEPOT MEDROXY PROGESTERONE ACETATE FOR POST-PARTUM CONTRACEPTION IN A TERTIARY CARE CENTRE IN EASTERN INDIA - Roy, Sudev; Patra, Sangita; CHALKRABARTY, Somajita (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Our aim was to determine the proportion of women accepting injection depot medroxyprogesterone acetate (DMPA) for postpartum contraception, its incidence of side effects, and discontinuation rates reasons for attrition. Methods: A prospective cohort study was conducted in the department of obstetrics and gynecology at a tertiary care hospital for 1 year. All eligible women were given a choice of contraceptive options after proper counseling for postpartum patients at the time of discharge and at 6 weeks, thereafter, and post-abortion patients immediately after MTP. A specially designed modified pro forma from the DMPA reference manual was used to collect the data of women attending the hospital. Result: A total of 240 women were included in the study. Most of the women (51.67%) were in the reproductive age group, 46.67% of women had 2 or more children, and most of the women (70.41%) were not used any family planning method earlier. The largest proportion of women (81.25%) were in the postpartum period. Irregular bleeding/spotting (39.08%) was the most common side effect. A larger portion of the women (36.5%) discontinued the injections due to side effects. Conclusion: It should be available as a first-line method to all who wish to opt for reversible methods of contraceptive.